The Verticillium dahliae SnodProt1-Like Protein VdCP1 Contributes to Virulence and Triggers the Plant Immune System - Zhang, Yi; Gao, Yuhan; Liang, Yingbo; Dong, Yijie; Yang, Xiufen; Yuan, Jingjing; Qiu, Dewen (Frontiers in Plant Science, 2017)
During pathogenic infection, hundreds of proteins that play vital roles in the Verticillium dahliae-host interaction are secreted. In this study, an integrated proteomic analysis of secreted V. dahliae proteins was performed, and a conserved secretory protein, designated VdCP1, was identified as a member of the SnodProt1 phytotoxin family. An expression analysis of the vdcp1 gene revealed that the transcript is present in every condition studied and displays elevated expression throughout the infection process. To investigate the natural role of VdCP1 in V. dahliae, two vdcp1 knockout mutants and their complementation strains were generated. Bioassays of these mutants revealed no obvious phenotypic differences from the wild-type (WT) in terms of mycelial growth, conidial production or mycelial/spore morphology. However, compared with the WT, the vdcp1 knockout mutants displayed attenuated pathogenicity in cotton plants. Furthermore, treating plants with purified recombinant VdCP1 protein expressed in Pichia pastoris induced the accumulation of reactive oxygen species, expression of several defence-related genes, leakage of ion electrolytes, enhancement of defence-related enzyme activity and production of salicylic acid. Moreover, VdCP1 conferred resistance to Botrytis cinerea and Pseudomonas syringae pv. tabaci in tobacco and to V. dahliae in cotton. Further research revealed that VdCP1 possesses chitin-binding properties and that the growth of vdcp1 knockout mutants was more affected by treatments with chitinase, indicating that VdCP1 could protect V. dahliae cell wall from enzymatic degradation, which suggests an effector role of VdCP1 in infecting hosts.